Effects of a physician‐ and pharmacist‐managed clinic on pain management in cancer patients in China. Issue 1 (4th April 2021) - Liu, Keke; Huang, Hangxing; Zhang, Lu; Huang, Yamin; Sun, Shusen; Chen, Xiaoping; Chen, Yao; Liu, Wenhui; Xiao, Jian
Abstract: In China, pharmacists have started to manage cancer pain at outpatient clinics. This retrospective study performed at a tertiary teaching hospital was aimed to evaluate the effects of a physician‐pharmacist joint clinic for cancer pain management. The study was performed between December 2016 and August 2019 and included 113 outpatients with moderate to severe cancer‐related pain. Patients were divided into two groups according to the clinic each patient visited: the physician‐pharmacist joint clinic (joint group, n = 59) or physician‐only clinic (usual group, n = 54). Brief Pain Inventory (BPI) and Morisky Medication Adherence Measure (MMAM) were used to collect data on pain intensity, interference and medication adherence. Pain Management Index (PMI) was also calculated. BPI, MMAM and PMI were assessed at baseline (patients' first visit, week 0) and week 4 follow‐up. The Chinese version of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire‐Core 30 (EORTC QLQ‐C30) was used to assess patients' health‐related quality of life (HRQoL) at week 4. The primary outcomes were the improvement in pain intensity, adequacy of pain management and medication adherence. The secondary outcome was the improvement in HRQoL. At week 4, compared to the usual group, the BPI pain intensity categories except the pain right now were significantly lower in the joint group: worst pain, 4 (3‐7) vs 6 (4‐8), P  = .020; least pain, 1 (0‐2) vs 2 (1‐3), P  = .010; average pain, 3 (2‐4) vs 4 (2‐5), P  = .023; pain right now, 2 (1‐3) vs 2 (0‐4), P  = .796. For the seven pain interference categories, there were no significant improvements in the joint group ( P  > .05). Significantly more patients achieved adequate pain control in the joint group than the usual group (( P  = .002). There was also a significant difference in medication adherence between the two groups ( P  = .001). There were no significant differences in HRQoL between the two groups. The study suggests that pharmacist participation in outpatient cancer pain management is associated with improvement of patients' pain control and medication adherence.